Bradykinin B2BKR receptor polymorphism and left-ventricular growth response. - Brull, D; Dhamrait, S; Myerson, S; Erdmann, J; Woods, D; World, M; Pennell, D; Humphries, S; Regitz-Zagrosek, V; Montgomery, H (2001)
Angiotensin-converting-enzyme (ACE) activity regulates left-ventricular growth. The deletion (D), rather than the insertion (I), ACE gene variant is associated with increased ACE activity and kinin degradation, and the absence (-) rather than the presence (+) of a 9 bp deletion in the gene encoding the bradykinin 2 receptor (B2BKR) is associated with greater gene expression. We determined the ACE and B2BKR genotype of 109 male army recruits, and measured their physiological left-ventricular growth response to a 10-week physical training programme. Mean left-ventricular growth was 15.7 g (SE 3.5) in those with ACE genotype D/D and B2BKR genotype +9/+9, but -1.37 g (4.1) in those with ACE genotype I/I and B2BKR genotype -9/-9 (p=0.003 for trend across genotypes). These results suggest that kinins regulate left-ventricular growth, mediating some of the effects of ACE in this regard.